2023
DOI: 10.3390/biomedicines11061702
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diosmin, Escin, and Bromelain on Human Endothelial Cells Derived from the Umbilical Vein and the Varicose Vein—A Preliminary Study

Abstract: In this study, we investigated the properties of human varicose vein (VV) endothelial cells (HVVEC) in comparison to the human umbilical vein endothelial cells (HUVEC). The cells were treated with three bioactive compounds with proven beneficial effects in the therapy of patients with VV, diosmin, escin, and bromelain. Two concentrations of tested drugs were used (1, 10 mg/mL), which did not affect the viability of either cell type. Escin led to a slight generation of reactive oxygen species in HUVEC cells. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…In addition, we demonstrated that treatment of red blood cells with diosmin and bromelain stimulated the biosynthesis of glutathione and thiols in RBCs. This mechanism may be important in the action of these substances in varicose veins, because, apart from other properties, these compounds contribute to the reduction of oxidative stress [57]. An increase in the level of oxidative stress parameters in plasma, e.g., TBARS, and protein carbonyls, as well as decreased catalase activity and thiol levels, were also observed in a group of patients with varicose veins compared to a group of healthy volunteers [151,152].…”
Section: Antioxidants and Oxidative Stress In Plasma And Red Blood Ce...mentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, we demonstrated that treatment of red blood cells with diosmin and bromelain stimulated the biosynthesis of glutathione and thiols in RBCs. This mechanism may be important in the action of these substances in varicose veins, because, apart from other properties, these compounds contribute to the reduction of oxidative stress [57]. An increase in the level of oxidative stress parameters in plasma, e.g., TBARS, and protein carbonyls, as well as decreased catalase activity and thiol levels, were also observed in a group of patients with varicose veins compared to a group of healthy volunteers [151,152].…”
Section: Antioxidants and Oxidative Stress In Plasma And Red Blood Ce...mentioning
confidence: 84%
“…These results demonstrated a higher stiffness of HVVEC plasma membranes compared to HUVEC cells. Differences in the fluidity of normal and pathological membranes may be the result of lipid-lipid and lipidprotein interactions or may be caused by oxidative stress occurring in the pathological vein [57]. Changes in membrane fluidity are closely related to the passive and active transport of substances across membranes into and out of the cells [58,59].…”
Section: Cellular Response In Inflammatory Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponins are included among a class of natural medicines called phlebotonics, which are used to treat thrombophlebitis and other venous insufficiencies, mainly varicose veins of the legs and hemorrhoids (Sirtori, 2001). They can be safely administrated by ingestion or topical application, and depending on the dose, they produce different phlebotonic effects, such as imparting rigidity and fluidity into the cellular membranes of the venous endothelial walls (Sirtori, 2001;Lorent et al, 2014;Gwozdzinski et al, 2023). Particularly referring to βescin extracted from chestnut seeds (A. hippocastanum), antiinflammatory, anti-edematous, and venotonic effects have been attributed to this natural compound (Sirtori, 2001;Gallelli, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical studies have been conducted to date (Underland et al, 2012), specifically confirming escin as a safe and effective phlebotonic to treat chronic venous insufficiency (CVI) (Pittler and Ernst, 2012;Dudek-Makuch and Studzińska-Sroka, 2015). In pathophysiological terms, the escin-based regulation of cell membrane rigidness seems to be the key factor for reducing varicose inflammation (Gwozdzinski et al, 2023). Although the etiology of inflammatory venous diseases is very complex, it involves genetic susceptibility, cellular responses, and environmental factors that cause vein wall inflammation, such as hypoxia, abnormal flow stresses, and venous blood stasis elicited by altered levels of nitric oxide and prostaglandins in circulation (Smith et al, 2006;Cogolludo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%